The influence of the ownership effect on Chinese children's learning performance: a comparative study between choosing and assigning ownership acquisition styles - Li, Taiping; Lu, Baoquan; Wu, Huifen (Frontiers in Psychology, 2025)
The cultural context can regulate the ownership effect, thus affecting learning performance and object memory. Previous studies have discussed the influence of ownership effect on children's learning based on the choosing and assigning ownership acquisition style. However, for Chinese children growing up in an interdependent cultural context, it is unclear the differences in the impact of ownership effects on learning performance in the two ownership acquisition styles when intimate others are involved in the learning process. In this study, an independent two-factor mixed experimental design was adopted: 2 (ownership acquisition style: choosing and assigning) × 3 (ownership condition: self, mother/friend/teacher, and others). Each experiment recruited approximately eighty third-grade Chinese students aged 7–9 years old. They were asked to place a series of pictures of themselves, intimate others (mother, friend, or teacher), and strangers in baskets according to color cues (assigning) or self-choice (choosing). They then completed a free-recall task. A repeated-measures analysis of variance was conducted on the correct free recall rate, and the results were as follows: Performance under the chosen ownership acquisition style was better than that under the assigned ownership acquisition style. There was no significant difference between the learning performance in the condition of mother and self-ownership, but both were higher than the learning performance in the condition of others-ownership. Learning performance in the self-ownership and friend-ownership conditions were significantly higher than that in the others-ownership condition, and performance in the self-ownership condition was significantly higher than that in the friends-ownership condition. Performance in the self-ownership condition was significantly higher than that in the teacher-ownership and others-ownership conditions, whereas the performance in the teacher-ownership condition was not significantly different from that in the others-ownership condition. Our findings showed that, for Chinese children, mothers' involvement in children's learning performance was just as beneficial as self-involvement in the ownership teaching situation. Although learning performance in the condition of friend-involvement was not as good as that for self-involvement, it can improve learning performance. However, learning performance was the poorest in the teacher-involvement condition. This research implicated ownership teaching as a teaching strategy that should be widely disseminated in interdependent cultural contexts, especially ownership teaching methods based on choosing. The simplicity, efficiency, and economy of its operation process will inspire educational researchers to fully explore the potentially more valuable tools that may exist in this “educational toolbox.” In addtion, it is necessary to fully leverage the roles of family education and peer-assisted learning in Chinese children's education. This also indicates that in the process of educational reform and policy formulation for Chinese children, the influence of culture should be fully considered.